Strategi Pemasaran Telur Bebek di Desa Sebalik Melalui Pendekatan Analisis SWOT - Heri Setiawan; Rosita Rosita; Fetty Maretha; Tika Handayani (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2024)
Marketing strategies are crucial for effectively and efficiently marketing products, especially for egg-laying duck breeders in Sebalik Village, located in one of the water areas in South Sumatra. A SWOT analysis is used to examine both external and internal factors in Sebalik Village, including strengths, weaknesses, opportunities, and threats. This research employs descriptive qualitative methods. According to the SWOT analysis, the duck egg marketing business is positioned in quadrant IV, indicating that a turnaround strategy focused on WO (weakness-opportunity) is the most appropriate. The WO strategy highlights the importance of surviving by addressing existing weaknesses and capitalizing on as many opportunities as possible. Steps that can be taken in this strategy include: 1) Increasing the Knowledge and Capabilities of Business Actors, namely providing training and education to business actors to increase their capacity in running a business. 2) Product and brand innovation, namely developing innovations in products, brands and packaging that reflect the characteristics of the product to make it more attractive in the market. 3) Use of social media and influencers such as using social media and influencers as a promotional tool to expand consumer reach. And 4) Selecting a strategic distribution location, namely determining distribution channels that are close to consumers to facilitate access and increase sales.